Promoting “batik eco-print” through training English digital storytelling (e-dst) by empowering local small medium enterprise perpetrators: a conservation strategy - Rustandi, Andi; Said, Iskhak; Sugiawardana, Ruli; Buang, Nor Aishah (Galuh International Journal of Community Service and Development, 2023)
Indonesian local cultural heritage is a worthwhile asset to develop in the recent era. It is an important industry generating millions of jobs and billions of dollars in revenue yearly. However, despite the tremendous economic and socio-cultural benefits, little attention is usually paid to its conservation and to developing innovative big-picture strategies to conserve and promote to be globally familiar. This perspective aims to compile some of the relevant global needs to explore alternative ways to conserve steps associated with the 2030 Agenda for Sustainable Development. From this perspective, it is conceptualized how emerging artificial intelligence (AI) and digital socio-technological models of conservation based on local culture “Batik Eco-print” through digital storytelling can represent an alternative transformative solution by going beyond the current global communication and technical limitations in the heritage conservation community, while also providing digital promotion to conservation practitioners, which can truly help the conservation process as the way promote local culture to be globally acknowledged. This article employed a qualitative research approach implementing a descriptive with a deductive research design. One of the results showed that social workers use digital media technologies that reflected the consistency of the social workers with the literature on social media engagement more generally. Another result showed that participants believed that their understanding of digital technology and digital storytelling was potential in reducing communication barriers in professional contexts.